Allocating conference delegates to workshops: A special timetabling problem - M. Sinclair; D.G. Esterhuyzen (ORiON, 2003)
The problem of assigning delegates to workshops at a conference can be formulated as a timetabling problem. Such an assignment must take into account the preferences of the delegates, as well as the number of participants each workshop can accommodate. This paper will report on a heuristic solution technique for a special case of such a problem. An implementation of the method for the solution of a real world problem will also be reported.